BIOADEQUATE PREPARATION OF COMPETITIVE SPECIALISTS OF CULTURE AND ART - Deyeva, Olga А.; Еryashkina, Marina V. (Otkrytoe Obrazovanie, 2016)
Expediency of harmonization of the relations of people valued, spiritual and practical is shown inter se and by the surrounding world. Cardinal reorganization of the system of education is suggested to begin with presentation of educational information in fundamentally new, natural, kind. The patterns are set of enriching of educational information intersubject connections, qualificatory building in “living fabric” of lesson of musical and literary fragments. It is shown that in the period of the bioadequate teaching organization of учебноof educator process walks up the level in creations of teacher and student.